Holistic Learning Models in Remote Areas: Enhancing Student Motivation through Local Wisdom, Parental Collaboration, Teacher Capacity, and Government Support - M, Usman; Hermansyah, Sam; ., Yusrianti; Said, Sunandar; Febrianti, Devy; Rizal, Andi (Journal of Ecohumanism, 2024)
This study explores a holistic learning model in elementary education that integrates local wisdom, parental collaboration, teacher capacity, and government support to enhance student motivation in remote areas of South Sulawesi, Indonesia. The research follows a quantitative approach, employing Structural Equation Modeling (SEM) with Smart PLS to analyze data collected through offline questionnaires from 159 respondents, including 18 school principals and 141 elementary school teachers. Results reveal that government support significantly boosts both teacher capacity (O = 0.64, P = 0.000) and student motivation (O = 0.36, P = 0.000). Teacher capacity plays a critical role in improving student motivation (O = 0.807, P = 0.000) and fostering parental collaboration (O = 0.289, P = 0.000). Surprisingly, a negative correlation was found between parental collaboration and student motivation (O = -0.289, P = 0.000), while local wisdom showed an insignificant impact on student motivation (O = -0.097, P = 0.215). Discussion suggests that government support and teacher capacity are key drivers of student motivation, though the complex dynamics of parental collaboration require further exploration. Conclusion: The study highlights the importance of teacher capacity and government involvement while recognizing the nuanced role of parental involvement. Future research should explore these factors across different cultural contexts, using mixed-methods approaches to provide a deeper understanding of the relationships and the role of cultural practices in motivating students.